The taxation of 'Influencers' in South Africa and in an international context - Smith, Carla (Department of Finance and Tax, 2025)
Social media has changed as a result of the digital economy's explosive expansion, turning it into a powerful tool for both individuals and businesses alike. Influencer marketing, a product of this digital era, has achieved remarkable success. With their dynamic and multifaceted lives, social media Influencers have become an integral part of the digital economy. However, existing international tax rules lack specific provisions addressing Influencers, raising questions about their tax treatment and the potential for treaty abuse. This underscores the necessity of exploring how the Influencers are to be taxed within the current legal frameworks, both from a local and international point of view. Following the introduction of fundamental concepts essential for understanding the activities and income generation means of Influencers, this document delves into an exploration of the local and international tax implications for these individuals. In the local context, an examination of current South African tax laws applicable to Influencers is undertaken. Additionally, in the international sphere, an in-depth analysis of their activities is conducted within the framework of the Organisation for Economic Co-operation and Development on Income and Capital Model Tax Convention (“OECD MTC”). Upon examination of the activities and income streams of Influencers from both a South African and international perspective, it became evident that their taxation is guided by existing legislation rather than specific provisions tailored for them. In South Africa, the classification of Influencers as employees or independent contractors holds crucial implications for their tax treatment. Notably, the taxation of promotional gifts, whether received for consideration or not, emerges as a critical aspect, subjecting Influencers to taxation due to their provision of marketing or advertising services. On the international front, existing rules, with the exception of the debate around Article 17 of the OECD MTC, are deemed sufficient for encompassing Influencer activities. The choice between Article 7 and Article 17 depends on the nature of the Influencer's activities. The various income streams of Influencers, from commission income to fees for services rendered and the sale of goods, fall within the scope of Article 7. The examination of Influencer activities under Article 17 is particularly relevant when they entertain followers through live social media posts. The conclusion underscores that Influencers face similar cross-border challenges as other taxpayers. Still, it emphasises the need for careful identification of their income streams to ensure proper application of double tax treaties and to avoid potential issues of double taxation or double non-taxation. The unique lifestyle of Influencers may lead to scenarios of double taxation, and them seeking visas in lower-tax jurisdictions since most of their income is subject to taxation in the Country where they are tax resident. The ongoing discussions regarding the taxation of Influencers are of crucial importance, particularly in light of evolving dynamics within the digital economy and their substantial potential for tax collection. This underscores the importance for Tax Authorities to provide clear guidance in navigating this intricate landscape for Influencers.